2001
DOI: 10.1002/nme.135
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐domain analysis of time‐integration methods for semidiscrete finite element equations—part II: Hyperbolic and parabolic–hyperbolic problems

Abstract: Time-integration methods for semidiscrete ÿnite element equations of hyperbolic and parabolichyperbolic types are analysed in the frequency domain. The discrete-time transfer functions of six popular methods are derived, and subsequently the forced response characteristics of single modes are studied in the frequency domain. Three characteristic numbers are derived which eliminate the parameter dependence of the frequency responses. Frequency responses and L 2 -norms of the phase and magnitude errors are calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Equations (3a) and (3b) indicate that the CR integration algorithm is explicit for both the displacement and velocity, making it well suited for application to real-time testing. Ramirez [20], Mugan and Hulbert [21,22] showed that integration algorithms for linear elastic structures can be expressed in the form of discrete transfer functions. A discrete transfer function is used in control engineering to represent the relationship between the output and the input of a discrete linear time-invariant system.…”
Section: Formulation For Unconditionally Stable Explicit Cr Integratimentioning
confidence: 99%
“…Equations (3a) and (3b) indicate that the CR integration algorithm is explicit for both the displacement and velocity, making it well suited for application to real-time testing. Ramirez [20], Mugan and Hulbert [21,22] showed that integration algorithms for linear elastic structures can be expressed in the form of discrete transfer functions. A discrete transfer function is used in control engineering to represent the relationship between the output and the input of a discrete linear time-invariant system.…”
Section: Formulation For Unconditionally Stable Explicit Cr Integratimentioning
confidence: 99%
“…see References [13] and [14]), and there is a tradeo in the frequency domain that has to be satisÿed by time integration methods [20]. Some of the existing higher-order accurate time integration methods are derived based on approximations to the exact solutions of semidiscrete equations that require the forcing terms and boundary conditions to be known; however, these functions may not be known exactly and it is common practice that values of forcing terms and boundary conditions are available only at discrete time steps.…”
Section: Introductionmentioning
confidence: 99%
“…One of the constraints in the frequency domain is that temporally discretized equation of a system cannot emulate the associated semidiscrete equation of the system beyond the Nyquist frequency = t, where t is the time step; furthermore, signiÿcant phase and magnitude errors occur as the frequency of the forcing terms approaches to the Nyquist frequency = t, e.g. see References [13] and [14]. In brief, it is impossible to resolve the response of a structure in response to inputs containing frequencies beyond the Nyquist frequency = t no matter what the order of accuracy of the time integration method is.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations